Facile synthesis of B and P doped g-C3N4 for enhanced synergetic activity between photocatalytic water splitting and BPA degradation. (26th April 2023) - Liu, Xuecheng; Yan, Linjie; Hu, Xiting; Feng, Hongli; Guo, Bingke; Ha, Xia; Xu, Hui
Abstract: A facile construction of B and P doped carbon nitride as a potential photo-catalyst for splitting water to generate hydrogen or oxygen and BPA removal under visible light. B and P doping are confirmed by a series of characterizations. As the symmetrical π-conjugated rings of g-C3 N4 could be destroyed by B and P doping to enhance the visible-light absorbance and n → π∗ electronic transition to provide a new pathway for the directional separation of photoexcited electrons to boost the photocatalytic activity. Significantly, the CN-BP catalyst demonstrates excellent H2 and O2 evolution rates of 4.0 mmolH2 h −1 g −1 and 0.3 mmolO2 h −1 g −1 under visible light, which is about ∼3.8 and 21.6 times higher than that of g-C3 N4, respectively. Notably, without sacrificial agent, the CN-BP could remove BPA completely by oxidation to generate 30 μmol h −1 g −1 H2 . Both DFT calculations and characteristic results reveal that B and P doped carbon nitride reduce band gap energy, improve light harvesting and separation rate of electron-holes carriers for upgrading the photocatalytic activity. Highlights: CN-BP catalyst demonstrates 3.8 and 21.6-fold increased activity for hydrogen and oxygen evolution, respectively. CN-BP photocatalyst could completely remove BPA to produce 30 μmol H2 per hour. B and P doping g-C3 N4 could enhance the optical properties by exciting n→ π∗ electronic transition.